O circuito espacial da indústria de cerâmica vermelha no seridó potiguar - Nascimento, Judicleide de Azevedo (2011)
This research has as an empirical universe, the productive territory of red ware in the Seridó region of Rio Grande do Norte. In the last years this territory has gone through a process of appropriation that has been substantially changing the environmental and social dynamism of the place. However, the industry of red ware has been focusing in some areas, mainly, in the county of Parelhas and Carnaúba dos Dantas. From this point of view, the aim of this work consists in analyze the use of these areas by the red ware industry and the transformations occurred with the expansion of the number of industries and the productivity raise, that requires bigger amounts of earthenware and wood, resources that are low in referred territory. As the result of this process, the suitable alternative has been to acquire inputs in other Rio Grande do Norte counties, as well as in Paraíba counties. To reach the proposed objective, the methodology of this work was consisted of bibliographic and empirical research, regarding the occupation that this activity covers in the Seridó region. From the information obtained during the research, it can be stated that the inputs to the production execution in the red ware industry are acquired in the geographic nearby lands. The analysis of the stages of the production(acquisition of raw material, production and commercialization) showed that the activity acts in a continuous area, having as principal consumer market other northeastern states and the state of Pará. The present study revealed that the pottery activity is set as untenable, because of non-stopping use of the argil and wood, resources that are vanishing from the area, which consume causes a many problems such as deforestation and erosion. Besides, the sale of productive lands for the red ware industries makes harder its good use by the familiar agriculturists in the development of agriculture and cattle raising activity, which for many times is the main economic activity of the place. The precariousness reveals in the constant accidents at work, that most of them are neglected by the local authorities, without any penalty to the industries. Therefore, the industry of red ware in Seridó uses the territory as a resource, leaving its environmental problems that my compromise the quality of life of the actual and future generations